Voting at Home Is Associated with Lower Cortisol than Voting at the Polls - Neiman, Jayme; Giuseffi, Karl; Smith, Kevin; French, Jeffrey; Waismel-Manor, Israel; Hibbing, John (PLOS ONE, 2015)
Previous research finds that voting is a socially stressful activity associated with increases in cortisol levels. Here we extend this research by investigating whether different voting modalities have differential effects on the stress response to voting. Results from a field experiment conducted during the 2012 presidential elections strongly suggest that traditional “at the polls” voting is more stressful, as measured by increases in cortisol levels, than voting at home by mail-in ballot or engaging in comparable non-political social activities. These findings imply that increased low-stress voting options such as mail-in ballots may increase political participation among individuals who are sensitive to social stressors.